A Review of the Problems and Difficulties in the India Fruits and Vegetables Supply Chain - Risa; Kanth (Global Journal of Food and Agribusiness Management, 2024)
Purpose- There are numerous problems and difficulties with India's whole fruit and vegetable supply chain. The supply chain of the Indian fruit and vegetable industry must be studied in order to identify potential obstacles and offer solutions. Therefore, the aim of this study is to explain the problems that are harming the Indian fruit and vegetable supply chain. In order to address the concerns and obstacles that were found, the authors also proposed the appropriate mitigation techniques. Design/methodology/approach- For this study, descriptive research was employed. The Fruits and Vegetables industry's supply chain has been described, and an effort has been made to pinpoint the problems affecting it. The current study attempts to explain the factors influencing the supply chain of the fruits and vegetables sector in India by conducting a thorough analysis of the basic and current literature. The literature has been categorized into several themes based on supply chain problems, and an effort has been made to determine the different elements that have an impact on the supply chain. Findings- The study discovered that infrastructure facilities, a fragmented supply chain, links and integration between partners, taxation issues, the cost of packaging materials, technology and techniques, and cold chain facilities Knowledge and awareness of farmers; standards for quality and safety; processing and value addition; inefficiencies in the supply chain; farmers' earnings; fresh product waste and supply chain losses; facilities for transportation; The fruits and vegetables industry has significant obstacles due to issues like demand and market data, which also have an impact on India's total agricultural development. Research limitations/implications- The authors may examine other sectors such as food processing facilities, cold chains, and other perishable goods like meat, dairy products, chocolate, drinks, etc., but they have solely focused on the fruits and vegetables market. Practical implications- In order to improve planning and management in the field of the supply chain for fruits and vegetables, decision makers and other stakeholders, including farmers, the state government, transporters, and food processing units, will benefit from resolving these problems. Originality/value- The majority of earlier research has been on broad concerns related to the supply chain for fruits and vegetables, such as cold chain and marketing effectiveness. A review of the supply chain, particularly in the F&V sector, is required in order to identify all the elements influencing it and offer mitigation methods. The vacuum in the literature on supply chain management for the fruits and vegetables industry is filled by this review.